The prevalence and pattern of enteropathogenic E. coli, shigella and salmonella among infants and young children in the Etimesğut rural area - Saatchi, Abduljabbar; Bertan, Münevver; Akman, Muvaffak; Türet, Sevgi (The Turkish Journal of Pediatrics, 1969)
The incidence of enteropathogenic E. coli was found to be five per cent of 100 children studied at the Etimesgut out-patient clinic. The incidence of enteropathogenic E. coli and Shigella was found to be 3.2 per cent and 0.8 per cent respectively among the 125 healthy children examined in Susuz.